Rainwater Harvesting for Drylands and Beyond Water-Harvesting Earthworks. - Lancaster, Brad. (Rainsource Press; U.S.A., 2013)
Its teachings should not just be applied to drylands. It's about using hydrological cycles to create and support sustainable landscapes, and the lessons are universal and useful wherever you live. This book is where to start with environmental restoration. His story of 'The Man Who Farms Water' in Africa is a microcosm and metaphor for the brilliant use of Nature's operating instructions. Most highly recommended!"
Includes bibliographical references and index.
Keywords: WATER HARVESTING; GARDEN and landscape design; Nature and ecology; Sustainable living and green design; Water supply and land use